Marx after the Kyoto school Utopia and the Pure Land - Kaye, Bradley (East Asian comparative ethics, politics and philosophy of law., 2022)
"Showing key connections between Marx's oeuvre and Buddhist thought, this book demonstrates connections between Marx and Nishida Kitaro, who many consider the key Japanese philosopher of the Kyoto School of Philosophy, the first modern philosophers in Japan"--